Muslim and non-muslim relationship an analysis of Qur’anic provision - Khan, Israr Ahmad (Islamic Perspective, 2015)
There is a gross misunderstanding on the part of both Muslims and nonMuslims the world over concerning the nature of Muslims’ attitude towards non-Muslims as expressly commanded by the Qur’an. It is claimed by the international media that the Qur’an inspires its followers to terrorize and kill others on the earth. This claim is based on misinterpretation of the Qur’anic statements on jihad and relationship with non-Muslims. Muslim scholars seem to have half-heartedly made effort to reinterpret such verses in the Qur’an. The Qur’an categorically states that it stands for peace, harmony, and justice on earth. How could it, then, be possible for the Qur’an to be the cause of chaos, mischief, and injustice in human relations? If the Qur’an seeks to establish justice and peace on earth, the claim that it commands its adherents to do away with non-Muslims is for sure untenable. Interpretation of the Qur’an requires application of valid principles. Two such principles are (1) “the Qur’an interprets the Qur’an”, and (2) “the sayings and doings of the Prophet (s.a.w.) constitute the key to understand the Qur’an”. The author will endeavor to put the Qur’anic statements on Muslim and non-Muslim relationship in their original context and analyze in the light of the overall message of the Qur’an and the Sunnah and Hadith of the Prophet (s.a.w.) with a view to reconfirming the Qur’anic command for the believers to have harmonious relationship with others.